Understanding exposure routes of endocrine disruptors in livestock - Gaddafi, S; Garba, M.G.; Yahaya, M.A. (Nigerian Journal of Animal Science, 2023)
This paper present review on various exposure routes of endocrine disruptors in livestock due to concern and wide usage of synthetic chemicals and other substances to mimic and interfere with natural hormones in livestock. Exposure to endocrine disrupting chemicals can have a lifelong effects and consequence to next generation livestock offspring. New endocrine disruptor chemicals continue to emerge and the negative and deleterious effects of such chemicals on growth, reproduction, and obesity constitute a public health issue in livestock production. The review indicates that there are various routes through which endocrine disrupting agent can get into animal body and disrupt the normal function of endocrine system: controversial use of synthetic steroid hormones, grazing contaminated pasture, drinking water, concentrate feed, inhalation EDCs substances, placental route, milk exposure and skin contact with product containing endocrine disruption chemicals. There is concern and call for animal science researchers to extensively diversify their studies in this area to come out with holistic solutions on how to minimize exposure and physio-reproductive consequences of endocrine disruptors in livestock.